Sequential Extraction of Polycyclic Aromatic Hydrocarbons and Metals from Airborne Particulate Matter - Abdollah, A.H.; Gheisari, M.; Talebi, S.M.; Abdollahi, A. (Asian Journal of Chemistry, 2010)
Polycyclic aromatic hydrocarbons (PAHs) and metals are two groups of air pollutants and monitoring of their atmospheric concentrations in mega cities is of extreme importance. Normally the concentrations of PAHs and metals are determined in different samples. The individual sampling and determination of these two groups of air pollutants is time consuming and it is difficult to investigate their relationship in a site or in the same sample. The possibility of analyzing of PAHs and metals in the same sample has been investigated. The results showed that the extraction of PAHs by supercritical fluid extraction before leaching of samples for metals have no effect on the concentration of metals.